Gestos de desenho em linhas de fuga : estratégias na construção do desenho performativo na arte contemporânea - Firmino, Ana Cláudia de Sena (2019)
This research proposes to think about a series of questions, inherent to drawing, which provides strategies for the construction of performative drawing in contemporary art. The use of the term performative drawing refers to the process of creation that e